Immunomodulation of Host Chitinase 3-Like 1 During a Mammary Pathogenic Escherichia coli Infection - Breyne, Koen; Steenbrugge, Jonas; Demeyere, Kristel; Lee, Chun Geun; Elias, Jack A.; Petzl, Wolfram; Smith, David G. E.; Germon, Pierre; Meyer, Evelyne (Frontiers in Immunology, 2018)
Chitin is a N-acetyl-d-glucosamine biopolymer that can be recognized by chitin-binding proteins. Although mammals lack chitin synthase, they induce proteins responsible for detecting chitin in response to bacterial infections. Our aim was to investigate whether chitinase 3-like 1 (CHI3L1) has a potential role in the innate immunity of the Escherichia coli (E. coli) infected mammary gland. CHI3L1 protein was found to be secreted in whey of naturally coliform-affected quarters compared to whey samples isolated from healthy udders. In addition, gene expression of CHI3L1 was confirmed in udder tissue of cows experimentally infected with a mammary pathogenic E. coli (MPEC) strain. Despite the known anatomical differences, the bovine udders’ innate immune response was mimicked by applying an experimental mouse model using MPEC or non-MPEC isolates. The effect of CHI3L1 expression in the murine mammary gland in response to coliform bacteria was investigated through the use of CHI3L1−/− mice as well as through treatment with either a pan-caspase inhibitor or chitin particles in wild-type mice. The local induction of CHI3L1 postinfection with different E. coli strains was demonstrated to be independent of both bacterial growth and mammary interleukin (IL)-8 levels. Indeed, CHI3L1 emerged as a regulator impacting on the transcytosis of Ly6G-positive cells from the interstitial space into the alveolar lumen of the mammary tissue. Furthermore, CHI3L1 was found to be upstream regulated by caspase activity and had a major downstream effect on the local pro-inflammatory cytokine profile, including IL-1beta, IL-6, and RANTES/CCL5. In conclusion, CHI3L1 was demonstrated to play a key role in the cytokine and caspase signaling during E. coli triggered inflammation of the mammary gland.